IMPLEMENTASI PEMBELAJARAN MATEMATIKA BERBASIS PETA KONSEP PADA MATA KULIAH KONSEP DASAR MATEMATIKA SD DITINJAU DARI KOMUNIKASI MATEMATIKA PRODI PGSD UNIVERSITAS QUALITY BERASTAGI - Novi Tari Simbolon; Ratna Wahyuni (Universitas Quality, 2022)
Mathematical communication ability is a very important cognitive ability to be measured in mathematics. This ability is in fact still relatively low. Students still have difficulty when working on story problems so as to improve communication skills using concept map-based mathematics learning. There are various factors that cause students' success in learning mathematics, one of which is the most basic, namely the way educators deliver learning material, how to deliver material that is considered inappropriate so that it has an impact on students' mathematics learning outcomes. Learning mathematics with lectures until now still dominates, so that students do not play an active role in learning. students tend to be bored and bored during learning because when educators enter class, they immediately encourage students to follow the learning path delivered by the teacher. Educators without prior to introducing mathematical concepts to be studied, students become confused and less interested in participating in teaching and learning activities. The basic solution offered from these problems is that educators are required to be able to create a creative learning model that can help students understand each material. One learning model that involves the creativity of students so that they can create ideas from each learning material so that it is expected to improve mathematics learning outcomes is a concept map-based learning model. Learning by applying concept maps, students become more motivated in learning, do not feel bored, and student activities are increasing, namely students are able to communicate what they find and can solve problems well.